2007
DOI: 10.1071/ah070362
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two colleges: do specialist trainees receive adequate hospital-based training?

Abstract: Background: Both medical and surgical trainees have a dual reliance on their specialist training college and their respective teaching hospitals to maintain standards in teaching and training. Although guidelines are in place for the administration of this teaching, hospital-based teaching has been minimally regulated. A review of trainee satisfaction with current levels of hospital-based training was performed, both to reflect the thoughts of trainees themselves and to highlight specific areas requiring impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Hospital-based teaching forms one of the pillars of most specialty training. A previous study 21 of basic surgical trainees (BSTs) and basic physician trainees (BPTs) showed clear differences between trainee satisfaction where BSTs reported significant dissatisfaction with hospital-based seminars, courses, material and skills courses in contrast with BPTs who were satisfied with their courses even though there were only a few. Their conclusion was that while the surgical college (Royal Australasian College of Surgeons) provided theoretical lectures, learning practical skills remained heavily reliant on local hospital resources via an apprenticeship model and case-based teaching.…”
Section: Trainee Satisfaction With Their Training Sitesmentioning
confidence: 97%
See 1 more Smart Citation
“…Hospital-based teaching forms one of the pillars of most specialty training. A previous study 21 of basic surgical trainees (BSTs) and basic physician trainees (BPTs) showed clear differences between trainee satisfaction where BSTs reported significant dissatisfaction with hospital-based seminars, courses, material and skills courses in contrast with BPTs who were satisfied with their courses even though there were only a few. Their conclusion was that while the surgical college (Royal Australasian College of Surgeons) provided theoretical lectures, learning practical skills remained heavily reliant on local hospital resources via an apprenticeship model and case-based teaching.…”
Section: Trainee Satisfaction With Their Training Sitesmentioning
confidence: 97%
“…Other studies emphasised the need to recognise the importance of 'sufficient, and capable clinical supervision, prioritising selection, training assessment and appropriate remuneration of clinical supervisors' who should also have protected time for the provision of safe, high-quality clinical supervision and teaching. 10,18,20,21,23 We advocate for directors of training and other clinical supervisors to have appropriate time for teaching and themselves receive adequate support and training to recognise and assist those trainees in difficulty.…”
Section: Reduced Trainee Satisfaction In Senior Yearsmentioning
confidence: 99%